2020
DOI: 10.1590/s0102-053620200207
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of vegetation indices and plant growth regulator use on the rooting of azalea cuttings

Abstract: ABSTRACT The objective of our study was to develop a protocol enabling the use of vegetation indices to evaluate the rooting of Azalea (Rhododendron pulchrum cv. Sweet) cuttings. Six root growth parameters were recorded after exposing those cuttings to rooting media for 47 days. Among plants with different soil-plant analysis development (SPAD) and normalized difference vegetation index (NDVI) values, those with higher values exhibited significantly higher number of roots, root length, and root dry wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
1
6
0
1
Order By: Relevance
“…Table 4 showed that there was no significant difference in any of the treatments of IBA and BioGroe applied to Bignay cuttings. This conforms with the findings where IBA, NAA and their combination treatments were not significant in rooting azalea cuttings (27).…”
Section: Percent Rootingsupporting
confidence: 92%
“…Table 4 showed that there was no significant difference in any of the treatments of IBA and BioGroe applied to Bignay cuttings. This conforms with the findings where IBA, NAA and their combination treatments were not significant in rooting azalea cuttings (27).…”
Section: Percent Rootingsupporting
confidence: 92%
“…This was also observed here in two barberry cultivars (Berberis thunbergii L. 'Maria' and 'Red Rocket') where root length increased due to spraying the cuttings with water IBA solution. Additionally, Hou et al [25] reported an increase in root number and length in azalea cuttings. In Rhododendron austrinum (Small) Rehder.…”
Section: Discussionmentioning
confidence: 97%
“…CF and GD were not used on RD III because of the large prop root diameter, and we only conducted RP for RD IV as the root diameters were too large to do CF or GD. We adopted Fractional 3-Factorial Designs (Plackett-Burman design) to test 24 relevant treatment combinations for their main effects [30]. The detailed treatment combinations were in listed in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…We used these 24 sets of relevant treatment combination values to make inference on the whole 48 values for the main effect of the 3 factors as a fractional factorial experiment [30,32]. Analysis of variance (ANOVA) was performed using R Studio version 1.2.1335 (R tools technology.…”
Section: Methodsmentioning
confidence: 99%